Teleconsultation at SUS during the COVID-19 pandemic in Brazil (Research, Society and Development, 2021)
Due to the Covid-19 pandemic, Brazil regulated the online medical care in order to provide remote attendance, elective and check-ups, avoiding the collapse of the Unified Health System. The purpose of this research was to investigate the offer to online medical care in SUS and multi professional assistence during the pandemic in the various states of the Brazil. It was performed a documentary, descriptive, quantitative and qualitative study. The data collection was made based on documents in public domain, found in officials websites of the states. It was observed that 100% of  the states has offered pre-clinical attendeance. With the regard of the avaiability of the online medical care to all citizens, there was a 100% reach in the Midwest and the Southwest states, 66% in the South, 57,1% in the North and 44,4% in the Northwest. It was given online medical care with doctors in all regions and with dental surgeon only in the Northwest and Southwest. The affordance of the Telehealth program has occured in 85,2% of the states. It can be concluded that the teleconsultation in SUS enabled citizens to acess health services remotely, especially during the Covid-19 pandemic, and that the biggest part of the brazilian states has offered the Telehealth Program.